IMPLEMENTASI JARINGAN SARAF TIRUAN UNTUK MENDETEKSI DAYA TAHAN TERHADAP STRES PADA MAHASISWA TINGKAT AKHIR DENGAN MENGGUNAKAN METODE BACKPROPAGATION - Dian Yudhawati & Nurul llmil Fadilah (Jurnal Psikologi, 2014)
Endurance or patience is the crucial factor for university students in completing their research. Having high endurance relates to the ability of facing stress, high motivation, and well ordered behavior. The artificial neural system has been built to detect this endurance level. When succeeding in identifying this endurance level, student will be able to manage his or her behavior toward completing research. The optimal endurance has been achieved when the artificial neural system has 0.75 learning constants and 60 hidden layers. At that condition, convergent stage or the SSE (sum square error) is ≤ 0.1, and the additional iterating is only 10,334. That optimal level is 100% accuracy in the regular examination and only 75% accuracy in the irregular examination.